2014
DOI: 10.1038/npjpcrm.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Studying the burden of community-acquired pneumonia in adults aged ⩾50 years in primary health care: an observational study in rural Crete, Greece

Abstract: Background:Community-acquired pneumonia (CAP) is a potentially life-threatening condition that often requires hospitalisation particularly in the elderly population or in patients with comorbidities.Aims:The aims of this study were to estimate the CAP frequency and severity in a well-defined primary healthcare setting in rural Crete, to record patient characteristics, their immunisation status and to estimate hospitalisation frequency and determinants.Methods:An observational study was designed and implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…CAP incidence in patients aged ≥ 65 years (19.13 per 1000 residents) was similar to that found in a retrospective assessment of CAP burden in Kielce, Poland (19.4 per 1000 residents) before the introduction of a municipal PCV7 vaccination program in young children [3]. The annual incidence rate of CXR+CAP in rural Crete, Greece was 2.4 per 1000 residents, lower than that observed in the current study (12.5 per 1000), potentially due to differences in disease incidence or variations in study design/data collection [22].…”
Section: Discussionsupporting
confidence: 84%
“…CAP incidence in patients aged ≥ 65 years (19.13 per 1000 residents) was similar to that found in a retrospective assessment of CAP burden in Kielce, Poland (19.4 per 1000 residents) before the introduction of a municipal PCV7 vaccination program in young children [3]. The annual incidence rate of CXR+CAP in rural Crete, Greece was 2.4 per 1000 residents, lower than that observed in the current study (12.5 per 1000), potentially due to differences in disease incidence or variations in study design/data collection [22].…”
Section: Discussionsupporting
confidence: 84%
“…CAP incidence varies considerably according to study approach, case definition, evaluated population and country with rates between <2 and >40/1000 person-years [2e11]. Generally, studies evaluating ICD-codes as CAP definition [4,5,7e9] found higher incidences (8e44 per 1000 py) than studies requiring x-ray confirmation (1.6e14 per 1000 py) [2,3,6,10,11]. Few studies reported incidence rates of outpatients with CAP; these found widely varying rates between 1.7 and 27 per 1000 py with highest rates in the US Medicare population [2,6,7,9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…These publications are summarised in online Supplementary Table S1. Of the included publications, 31 were prospective or surveillance [5,21,25,28,30,33,38,40,41,46,49 National population-based epidemiologic surveillance data for pneumonia were available from Norway [54], Portugal [58] and Spain [59,75,77]. As observed by Tichopad and colleagues [29], epidemiologic data in Central and Eastern Europe were predominantly collected from hospital settings, and there was a lack of data on outpatient CAP, with the authors instead using inpatient-to-outpatient ratios from a retrospective chart review to estimate outpatient incidence in the Czech Republic, Hungary, Poland and Slovakia.…”
Section: Studies Includedmentioning
confidence: 99%
“…[5,25,28,29,[35][36][37][39][40][41]46,49,51,53,55,64,69,72,84,88,89,91,93]. The lowest incidence of all-cause pneumonia was reported in Spain between 1999 and 2001 in patients aged 15-44 years…”
mentioning
confidence: 98%